Fresh Properties and Strength Development of Cement Mortar Using Nitrite-based Accelerator and Chemical Admixtures - Inoue, Masumi; Choi, Heesup; Sudoh, Yuhji (Proceedings of Engineering and Technology Innovation, 2018)
A nonfreezing agent prevents initial frost damage by simplified curing and also promotes early strength development. In general, a nitrite-based accelerator is used as the main component of this nonfreezing agent. When a large proportion of a conventional accelerator is used, the slump loss increases because the setting and hardening processes are strongly enhanced. In addition, these conventional accelerators may not be sufficiently effective at temperatures of -10 °C or less. Therefore, the fresh properties and strength development of cement mortars when using a nitrite-based accelerator and chemical admixtures in a low-temperature environment are examined. The objective is to develop a high-performance nonfreezing agent. This paper presents the contributions of the nitrite-based accelerator and two types of high-range water-reducing agents, used in combination. From the investigation, it was confirmed that the change in the mortar flow can be suppressed by combining two types of high-range water-reducing agents with a nitrite-based accelerator, even after the passage of 60 min after mixing. Furthermore, the mix was found to contribute to not only the initial strength but also toward maintaining the good strength for a longer time.